Challenges and Prospects of Entrepreneurship Development and Job Creation For Youth: A Case Study of Birgunj, Nepal - Ghimire, Shiva Raj; Chaudhary, Dipendra Kumar (Interdisciplinary Journal of Management and Social Sciences, 2021)
This research paper is focused on youth employment and entrepreneurship development in Nepal. The objectives of this research paper are to investigate the obstacles that young people encounter when setting-up their businesses and to assess the issues related to youth unemployment in Birgunj, Nepal. This study adopted a descriptive research design and quantitative research methodology. 62 sample sizes was randomly selected from a population of 124 young entrepreneurs from different Small and Medium Enterprises (SMEs) and industries, who formally registered their businesses on Birgunj Chamber of Commerce and Industries (BiCCI) at Birgunj, which promotes and develop entrepreneurship among youth in Birgunj.               The findings were illustrated in tables, bars and pie charts, and the objectives of this study were met. The conclusion of this study revealed that most important obstacles that young entrepreneurs of Birgunj encounter while setting up their businesses, and subsequently operating their businesses include; financial constraint is the most critical bottleneck to start up a new business, lack of support structures, ineffective programs of Nepal government to support entrepreneurial development in Birgunj, high cost involvement and unclear business registration process, lack of business management skills, lack of business resources. The young entrepreneur is suffering from unfair competition. However, involvement of youth in entrepreneurial activities is also encouraging.